KAJIAN STABILITAS TERMAL DAN KARAKTER KOVALEN ZAT PENGAKTIF PADA ARANG AKTIF LIMBAH GERGAJIAN KAYU MERANTI (Shorea spp) - Koleangan, Harry S. J.; Wuntu, Audy D. (Sam Ratulangi University, 2008)
A research considering the role of thermal stability and covalent character of activating agent on meranti timber sawmill-waste activated carbon using H3PO4 and CaCl2 as activating agents had been conducted. The result showed that activating agent having better higher covalent character yielded highest-adsorption activated carbon.